Augmenter of liver regeneration inhibits apoptosis of activated human peripheral blood lymphocytes in vitro. (5th February 2013) - Wang, Na; Sun, Hang; Shen, Yan; Li, Xiao-fang; Pan, Tao; Liu, Guang-liang; Liu, Qi
Abstract: Regulating apoptosis of lymphocytes is an effective strategy for treatment of lymphocyte-mediated diseases. Recently it has been demonstrated that augmenter of liver regeneration (ALR), an enigmatic protein presented ubiquitously in multiple forms among eukaryotes, possesses potent anti-apoptotic activity and supports proliferation of a variety of cells. However, its action on lymphocytes and the underlying mechanism are not completely understood. In this study, we analyzed the effects of recombinant human ALR (rhALR) on apoptosis of human lymphocytes activated with concanavalin A (ConA). Our results showed that rhALR inhibited apoptosis of ConA-activated lymphocytes and revealed reductions in the percentage of apoptotic cells, caspase-3 activation and PARP cleavage in cells treated with rhALR. Furthermore, the BAX/BCL-2 and cytosol/mitochondria cytochrome c ratios were decreased in the intrinsic death pathway and the activation of caspase-8 was also decreased in the extrinsic death pathway in activated lymphocytes treated with rhALR. In addition, rhALR significantly reduced the quantity of interleukin-2. These results demonstrated that rhALR has anti-apoptotic effects on activated lymphocytes through the activation of several apoptosis-related signaling pathways, and shed some light on the effects of rhALR on modulation immune reactions.